Saluran Distribusi dan Promosi terhadap Volume Penjualan Motor Honda CB 150R - Rudi Eduar; Nidyawati Nidyawati (IPM2KPE, 2021)
This study aimed to determine the effect of distribution channels, promotions, and the influence of both (distribution and promotion channels) on the sales volume of Honda CB 150 R motorcycles at PT. Astra International TBK. Nature Fence Branch. The method used in sampling in this study uses Time Series data. The data analysis method used is the Data Prerequisite Test (Normality Test, Multicollinearity Test, Linearity Test), Descriptive Statistics Test, Inferential Statistical Test (Multiple Linear Regression, Correlation Coefficient, Coefficient of Determination), and Hypothesis Testing (t Test and F Test). The results showed that the value of t count distribution channel is smaller than t table (3,597 > 4,303). Meanwhile, promotion, and the influence of both (distribution and promotion channels) on sales volume sequentially have a value of t count > t table (4.504 > 4.303; 48.236 > 19.0). The conclusion is that the distribution channel has no effect on the increase in motorcycle sales volume. Meanwhile, promotion, and the influence of both (distribution and promotion channels) were able to increase the sales volume of Honda CB 150 R motorcycles. Keywords: Distribution Channel, Promotion, Sales Volume